Proceedings of the 8th ACM Conference on Electronic Commerce 2007
DOI: 10.1145/1250910.1250924
|View full text |Cite
|
Sign up to set email alerts
|

Strong equilibrium in cost sharing connection games

Abstract: In this work we study cost sharing connection games, where each player has a source and sink he would like to connect, and the cost of the edges is either shared equally (fair connection games) or in an arbitrary way (general connection games). We study the graph topologies that guarantee the existence of a strong equilibrium (where no coalition can improve the cost of each of its members) regardless of the specific costs on the edges.Our main existence results are the following: (1) For a single source and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…They showed that for the unrelated machine scheduling games the Strong Price of Anarchy is at most 2m − 1, where m is the number of machines and that strong equilibria always exist. Later, Epstein et al [10] showed that the Strong Price of Anarchy of cost sharing games is Hn = O(log n), same as our bound for Subgame Perfect Equilibria. Strong Equilibria assume collective rationality, and requires players to collaborate, while Spe assumes only individual rationality.…”
Section: Introductionsupporting
confidence: 74%
“…They showed that for the unrelated machine scheduling games the Strong Price of Anarchy is at most 2m − 1, where m is the number of machines and that strong equilibria always exist. Later, Epstein et al [10] showed that the Strong Price of Anarchy of cost sharing games is Hn = O(log n), same as our bound for Subgame Perfect Equilibria. Strong Equilibria assume collective rationality, and requires players to collaborate, while Spe assumes only individual rationality.…”
Section: Introductionsupporting
confidence: 74%
“…In particular, our model is a special case of a K-capacitated network cost-sharing game with a simple structure of n parallel links and non-anonymous cost functions such that a strategy profile of the users in the network game corresponds to a coalition structure 2 . However, the key difference of our model from those in [7], [11], [15] is that we consider replaceable resources from a large pool of available resources, such that a subset of deviating users can always form a new coalition, independent from other users. This is not true in general network cost-sharing games, when there are limited resources (e.g., links) that a deviating coalition of players can utilize, and it may not be possible to form arbitrary coalitions independent from others.…”
Section: Related Workmentioning
confidence: 99%
“…It is also worth mentioning how our results of usage based cost-sharing relate to cost-sharing with anonymous cost functions in network design games [7] or connection games [11]. On one hand, our model is simpler as we do not assume connectivity requirements in a network, but only an abstract setting that allows arbitrary coalitions up to a certain capacity (but we allow non-anonymous cost functions).…”
Section: Related Workmentioning
confidence: 99%
“…For example, [27] showed that in a network formation game with single-source and multiple-targets played on a network that is not an SPP network, there is no strong PNE. [15] showed that in a game on an SPP network there always exist a strong PNE. Moreover, [20] showed that in network formation games, even if a strong PNE exists, not every beneficial coordinated deviations sequence converges to one.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%